LEXICAL DEVIATIONS OF THE TRANSLATED VERSION OF THE FAIRY TALE ENTITLED “THE ORIGIN OF GOOSES HAVE LONG NECK” (BILINGUAL VERSION: INDONESIAN-ENGLISH) SERI I - IRIANA, TRINIS (Jurnal Ilmiah Mahasiswa FIB, 2013)
Abstract-Translation becomes the basic requirement in exchanging process of information in the world. Fairy tale is a kind of learning media in the form of books for children which is written in Indonesia and is translated into English. In this case, the translators sometimes make deviations in translated work such as a fairy tale. Fairy tales are rarely considered as the data research to be analyzed. Some researchers pay more attention to analyze novels, poems, and films as the sample of data than fairy tale, perhaps, because the style of fairy tale is more imaginative, literal, and more simple than another literary text.The researcher is intended to find out the types of lexical errors in this study by using Peter Newmark theory and Nida theory. The study applies the descriptive qualitative research method in textual or document analysis. The data of the research are the sentences and utterances that contain errors in lexical type.This research concludes that errors or deviations can cause or create different meaning from the original text which is read by the reader. The greatest errors occur when the structure in the sentence of target text is not complete. It can be said that English language must notice grammar, and it must be natural.